2017
DOI: 10.4172/2471-2728.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Ureide Content of Guar under Influence of Hexaconazole and Triazophos

Abstract: The important part of regular human diet is vegetable, which supply minerals and nutrients for maintenance of health. India is first rank producer of guar comprise 83% of total world production but these are affected by diseases like leaf spots, leaf blotch and insect pest such as serpentine leaf miners, hairy caterpillars and jassids. The major biotic constraint in vegetable production is pest problem. Application of pesticides has now become a common practice in modern agriculture. Chemicalization of agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Fungicides also adversely affect the function and composition of soil enzymes, as well as microbial respiration, biomass production, diversity, and function [ 11 , 12 ]. Among fungicides, hexaconazole (HEXA), for example, has been found to adversely affect the various metabolic activities of plants [ 13 ]. Additionally, repeated use of fungicides has led to the emergence of resistance among fungal phytopathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Fungicides also adversely affect the function and composition of soil enzymes, as well as microbial respiration, biomass production, diversity, and function [ 11 , 12 ]. Among fungicides, hexaconazole (HEXA), for example, has been found to adversely affect the various metabolic activities of plants [ 13 ]. Additionally, repeated use of fungicides has led to the emergence of resistance among fungal phytopathogens.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hexaconazole, a broadspectrum systemic fungicide, is used to manage phytopathogenic fungi 12 on the one hand, while it negatively affects the BNF, ureide levels, N transformation and overall performance of leguminous plants on the other hand. 13,14 Also, it decreases chlorophyll and carotenoid pigment formation by legumes, for example, Phaseolus vulgaris. 15 In yet another study, the fungicide pyrimorph has been found to strongly inhibit the electrontransport reactions of chloroplasts and thus damages the physiological machinery of whole plants.…”
Section: Introductionmentioning
confidence: 99%
“…Plant treatment with certain fungicides reduced or stopped the formation of nodules and disrupted nitrogen fixation. For example, hexaconazole is used to control phytopathogenic fungi [77] but negatively affects biological nitrogen fixation, ureide levels, nitrogen transformation, and the overall yield of legume crops [78,79]. Previously, it was shown that the use of the tetramethylthiuram disulfide (TMTD) fungicide reduced the nodule number in pea laboratory lines Sprint-2 and SGE, as well as in the cv.…”
Section: Discussionmentioning
confidence: 99%